Approaching the theoretical capacity limit of Na2FeSiO4-based cathodes with fully reversible two-electron redox reaction for sodium-ion battery. (December 2020) - Guan, W.H.; Lin, Q.Y.; Lan, Z.Y.; Pan, W.L.; Wei, X.; Sun, W.P.; Zheng, R.T.; Lu, Y.H.; Shu, J.; Pan, H.G.; Yan, M.; Jiang, Y.Z.
Abstract: Orthosilicate compounds are emerging as a promising class of low-cost and intrinsically safe cathodes due to the strong inductive effects of polyanion groups for rechargeable sodium-ion batteries. However, enabling two-electron redox reaction and actualizing the appealing high theoretical capacity of ∼270 mAh g −1 for orthosilicates remain challenging. Here, fully reversible two-electron redox reaction in sodium iron orthosilicate cathodes by fluorine doping are reported. Owing to the unlocking of the Fe 3+ /Fe 4+ redox couple, F-doped Na2 FeSiO4 displays exceptionally high capacity of 271 mAh g −1 that has never been reported for polyanionic cathodes. Based on the newly built crystal structure model of triclinic phase, fluorine doping is demonstrated to greatly promote charge redistribution and accelerate the electron exchange, hosting more sodium ions in the framework and stabilizing Fe 4+ containing intermediate phases thermodynamically. The zero-strain characteristics of fluorine-doped orthosilicate ensure its excellent cycling stability with 93.7% capacity retention over 200 cycles. The successful unlocking of the trapped sodium in orthosilicates provides valuable insights and opens up a new avenue for the development of high capacity cathode materials for rechargeable batteries. Graphical abstract: Fully reversible two-electron redox reaction in orthosilicate cathodes by fluorine doping are reported. With the effect of promoting charge redistribution and accelerating the electron exchange, F-doped Na2 FeSiO4 displays exceptionally high capacity of 271 mAh g −1 that has never been reported for polyanionic cathodes based on Fe 2+ /Fe 4+ redox couple. Image 1